The impact of single nucleotide polymorphisms, cytokine and microrna profiling on susceptibility to preterm birth / Immaculate Mbongo Langmia - Immaculate, Mbongo Langmia (2015)
Preterm birth (PTB) is the single largest cause of neonatal mortality and morbidity worldwide. Genetic factors have been implicated in the occurrence of PTB. Single nucleotide polymorphisms in the vascular endothelial growth factor A, interleukin 1, interleukin 6, oxytocin receptor and progesterone receptor genes have been implicated in biological pathways that lead to preterm birth. Transcriptomics regulators such as microRNAs that regulate the expression of target genes are shown to play a vital role in PTB. Proteomics biomarkers including inflammatory cytokines such as tumor necrosis factor alpha, interleukins, vascular endothelia growth factor A are also shown to be associated with the risk of preterm birth. Racial and ethnic disparities in PTB have been attributed to differences in genetic components, proteomics content and variability in miRNA regulation of gene targets across populations. In this study, we aim to investigate the impact of genetic polymorphisms of various candidate genes on the risk of PTB, and determine the differential profiling of cytokines and miRNAs in the Malaysian population. A total of 664 women with spontaneous preterm (n =132) and term (n = 532) delivery were enrolled in this study. Genotyping was carried out using Sequenom MassARRAY® platform. Cytokine levels were measured using the ProcartaTMcytokine assay technology. The differential miRNA profiles between the preterm and term group were carried out using Affymetrix® GeneChip® miRNA 3.0 Array and further validated using quantitative polymerase chain reaction. Data were analyzed using SPSS version 22.0 statistical software, Expression console software and TAC software. Significant associations were observed between AKAP10 rs119672, AKAP10 rs169412 polymorphisms and reduced risk of PTB in the ethnic group (Malays). A significant association was also observed between iv VEGFA rs2010963 (OR 1.8, P =0.004), PGR rs660149 (OR 2.3, P = 0.011) and increased risk of PTB in the Malays, and finally IL1R2 rs2072476 (OR 3.78, P = 0.017) was associated with reduced risk of PTB in the Indian ethnic group. These polymorphisms may have potential roles in PTB complications in this population. This study also determined differential inflammatory cytokines in Malay women with spontaneous preterm and term delivery. For proteomics analysis, high levels of six specific cytokines including TNFA IL16, IFNG, MCP-3, Fractalkine and IL-17A were significantly associated with PTB. In conclusion, this study suggests that specific genetic variants and protein biomarkers have important roles for patient susceptibility to PTB among Malaysian women. This study also demonstrates that variability in the occurrence of PTB among Malaysian women may be attributed to the differences in their genetic makeup, thus in addition to other environmental confounders, genetic makeup and the downstream molecular entities involved in proteomics levels need to be greatly considered in this population. Prior information on the genetic and proteomic profiles of patients might lead to development of new diagnostic and treatment procedures for women who are at risk of PTB. If high risk women can be identified early in the pregnancy, intervention can be employed to avoid PTB in these women. This will help to prevent neonatal mortality and morbidity.